Pengaruh Interaktifitas dan Influencers terhadap Purchase Decision melalui mediasi Customer Engagement di Live shopping Tiktok - Gina Anindita; Henny Welsa; Ambar Lukitaningsih (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2026)
This study investigates the effects of interactivity and influencers on purchase decisions mediated by customer engagement in TikTok live shopping. The growth of social commerce has shifted consumer behavior toward interactive, real-time shopping experiences that blend entertainment and transaction. TikTok Live Shopping enables direct interaction among hosts, influencers, and viewers, potentially shaping engagement and buying outcomes. Using a quantitative survey approach, data were collected through an online questionnaire from 97 respondents who had previously watched and purchased via TikTok live streams, selected through purposive non-probability sampling. Data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS. The study is expected to demonstrate that higher interactivity and credible influencers enhance customer engagement, which in turn positively influences purchase decisions. The findings contribute to social commerce and marketing literature and provide guidance for businesses and content creators to optimize live-streaming strategies that foster engagement and drive purchases.